Rate and Predictors of Bacteremia in Afebrile Community-Acquired Pneumonia - Forstner, Christina; Patchev, Vladimir; Rohde, Gernot; Rupp, Jan; Witzenrath, Martin; Welte, Tobias; Burgmann, Heinz; Pletz, Mathias W (Chest, 2020)
Although blood cultures (BCs) are the "gold standard" for detecting bacteremia, the utility of BCs in patients with community-acquired pneumonia (CAP) is controversial. This study describes the proportion of patients with CAP and afebrile bacteremia and identifies the clinical characteristics predicting the necessity for BCs in patients who are afebrile. Bacteremia rates were determined in 4,349 patients with CAP enrolled in the multinational cohort study The Competence Network of Community-Acquired Pneumonia (CAPNETZ) and stratified by presence of fever at first patient contact. Independent predictors of bacteremia in patients who were afebrile were determined using logistic regression analysis. Bacteremic pneumonia was present in 190 of 2,116 patients who were febrile (8.9%), 101 of 2,149 patients who were afebrile (4.7%), and one of 23 patients with hypothermia (4.3%). Bacteremia rates increased with the CURB-65 score from 3.5% in patients with CURB-65 score of 0 to 17.1% in patients with CURB-65 score of 4. Patients with afebrile bacteremia exhibited the highest 28-day mortality rate (9.9%). Positive pneumococcal urinary antigen test (adjusted OR [AOR], 4.6; 95% CI, 2.6-8.2), C-reactive protein level > 200 mg/L (AOR, 3.1; 95% CI, 1.9-5.2), and BUN level ≥ 30 mg/dL (AOR, 3.1; 95% CI, 1.9-5.3) were independent positive predictors, and antibiotic pretreatment (AOR, 0.3; 95% CI, 0.1-0.6) was an independent negative predictor of bacteremia in patients who were afebrile. A relevant proportion of patients with bacteremic CAP was afebrile. These patients had an increased mortality rate compared with patients with febrile bacteremia or nonbacteremic pneumonia. Therefore, the relevance of fever as an indicator for BC necessity merits reconsideration.